This Week! Alamogordo, NM. (Alamogordo, New Mexico, 1947)
Alamogordo is the center of a magnificent scenic area, a mecca for tourists and the 1947 summer season is expected to exceed all former years.
An information booklet on Alamogordo, NM and information on hotels and other places to stay and see throughout New Mexico.
Master list item # 5
File location is in the New Mexico Cities and Towns
Keywords: Alamogordo, New Mexico; Hotels -- Alamogordo, New Mexico; Guest Ranch Directory; advertisements; Shopping roundup; Taos, New Mexico; Hotel Directory; restaurants -- Alamogordo, New Mexico -- Albuquerque, NM -- Santa Fe, NM